2016
DOI: 10.1136/tobaccocontrol-2016-053166
|View full text |Cite
|
Sign up to set email alerts
|

Australia's plain tobacco packs: anticipated and actual responses among adolescents and young adults 2010–2013

Abstract: The actual response of youth to plain packaging was greater than anticipated prior to their introduction, and support for plain packaging increased from preimplementation to postimplementation among all groups of youth. Jurisdictions planning to implement plain tobacco packaging should be encouraged by these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 36 publications
4
22
0
Order By: Relevance
“…It is furthermore consistent with the finding of a recent study 22 that provides 'evidence that a considerable proportion of young smokers tried to quit or thought about quitting as a result of the new Australian tobacco packs in the period following their introduction'.…”
Section: Logistic Regression Analysissupporting
confidence: 80%
“…It is furthermore consistent with the finding of a recent study 22 that provides 'evidence that a considerable proportion of young smokers tried to quit or thought about quitting as a result of the new Australian tobacco packs in the period following their introduction'.…”
Section: Logistic Regression Analysissupporting
confidence: 80%
“…The policy recognizes that on-pack brand imagery has positioned tobacco use as an aspirational behaviour and fostered uptake among young people, 5 transforming tobacco packages from attractive display items to highly unappealing articles. Evidence from Australia shows standardized packaging and larger pictorial warning labels have reduced smoking’s appeal among young people, 6 increased demand for cessation support 7 and decreased smoking prevalence. 8 Evaluations confirm predictions from experimental and other studies used to support the introduction of this policy.…”
mentioning
confidence: 99%
“…Several participants demonstrated aversive reactions to the health warnings, including asking for them to be covered, stating that they would put the cigarettes in another container so that they would not see the health warning, or not wanting to have the packet in their hand or pocket. Covering or hiding cigarette packs from others or feeling uncomfortable have been identified as markers of social denormalization [8]. In Australia, 8 months after standardized packs were introduced, one in four young smokers reported one of these responses that indicated feelings of social denormalization [8].…”
Section: Discussionmentioning
confidence: 99%
“…As more countries ban or restrict tobacco marketing, tobacco companies have focused their attention and promotional budgets on retail point-of-sale displays and cigarette branding and packaging [5][6][7]. These marketing strategies have created cigarette brand images that young smokers use as a form of symbolic consumption whereby the cigarette brand, and its perceived positive attributes (the brand heuristic), is used to construct and project a desirable identity to peers and others in their social worlds [8][9][10][11][12]. Systematic reviews of research with young people, including qualitative studies and experimental study designs involving 'mocked-up' cigarette packs with different features, have concluded that implementing standardized packaging which remove pack design elements would: reduce the appeal of cigarette packs and cigarettes; increase the prominence and salience of health warnings; and reduce the pack's ability to mislead about product harm [13][14][15].…”
Section: Introductionmentioning
confidence: 99%